Fascinating animal facts : featuring whales, elephants, bears, wolves, monkeys, turtles, snakes, birds, bees, ants and many, many more... - Klevansky, Rhonda; Taylor, Barbara, 1954- ([New York, N.Y.] : Hermes House, 2007)
This natural history book is illustrated with more than 1200 color pictures by some of the world's best wildlife photographers. It examines a huge range of incredible animals from tiny insects, beetles, bugs, spiders, moths and butterflies to snakes, birds of prey, wolves, dogs, horses, mighty bears, crocodiles and elephants. Each animal is examined in turn, with an introductory section followed by a detailed look at how they function, from their physical make-up, such as bones, teeth, skin, scales or fur, to how they use their brain and senses to find food, communicate or seek mates.
Keywords: Animals -- Miscellanea; Animals -- Miscellanea